2008
DOI: 10.1093/ejechocard/jen135
|View full text |Cite
|
Sign up to set email alerts
|

Tako-Tsubo syndrome in a pregnant woman

Abstract: We describe a rare case of Tako-Tsubo syndrome which occurred in a young woman at the beginning of pregnancy, who presented cardiac arrest at onset. In this case, the transient left ventricular ballooning involving both mid and apical segments, in absence of coronary artery disease, produced a severe impairment of cardiac function with typical echocardiographic and electrocardiographic findings. The favourable outcome, despite the sudden cardiac death at the beginning, raises further questions on this new kind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Several general observations have been made in Japan [5,6,7,8,9,10]. D’Amato et al [11] reported pregnant woman with TT cardiomyopathy who did not exhibit coronary artery disease. However, she did have severe impairment of cardiac function with typical ECHO and ECG findings.…”
Section: Discussionmentioning
confidence: 99%
“…Several general observations have been made in Japan [5,6,7,8,9,10]. D’Amato et al [11] reported pregnant woman with TT cardiomyopathy who did not exhibit coronary artery disease. However, she did have severe impairment of cardiac function with typical ECHO and ECG findings.…”
Section: Discussionmentioning
confidence: 99%
“…Only six patients have been reported including the present patient: TTS occurred in the first to second trimester in four patients and in the third trimester in two patients (Table 1). [4][5][6][7][8] In the present patient, TTS occurred concomitantly with PE, leading to a poor neonatal outcome. Although previous reports on pregnancy-associated TTS showed a good maternal outcome, antenatally occurring TTS complicated by severe PE may become critical for fetuses.…”
Section: Discussionmentioning
confidence: 59%
“…Only six patients have been reported including the present patient: TTS occurred in the first to second trimester in four patients and in the third trimester in two patients (Table ) . In the present patient, TTS occurred concomitantly with PE, leading to a poor neonatal outcome.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Patients affected by the disease are predominantly postmenopausal women who experience intense emotional or physical stress and subsequently develop chest pain and dyspnea [5] . Although cases of TCM in young women during pregnancy and even during delivery have already been described [6][7][8] , this entity in young premenopausal women appears to be rather unusual.…”
Section: Introductionmentioning
confidence: 83%